Taṭbīq Tiknūlūjiya Ta’līm al-Lugah al-‘Arabiyyah : Mafhūmuha wa Waẓāifuha wa Ahdāfuha wa Mabādiuha - Sahkholid Nasution (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Arabic learning -like other learnings- requires technology as a systemic effort in designing, developing, implementing and evaluating the whole learning process. The implementation of technology in Arabic learning is expected to be able to answer most of the problems experienced by teachers and students in Arabic learning, because technological learning can help teachers in delivering materials. Morefover, learners can absorb the materials maximally as well. This sudy is a conceptual thinking using a descriptive-analysis method. The conclusion of this study is the application of technology in Arabic learning is an attempt to overcome problems in Arabic learning, because learning technology is absed on some principles, namely systemic approach (al madkhal al-nizhamiy), student-oriented, and the use of learning resources optimally.